Cholinesterase inhibitors for the treatment of delirium in non-ICU settings - Yu, Ailan; Wu, Shanshan; Zhang, Zongwang; Dening, Tom; Zhao, Sai; Pinner, Gillian; Xia, Jun; Yang, Daogui (Wiley, 2018)
Background